The correllation between incidence rate of pertussis and vaccination rate of children from 1998 to 2016 in Poland - Czarnota, Jakub; Skubel, Tomasz; Dobrzyński, Michał; Sokół, Dorota; Standyło, Arkadiusz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2019)
Introduction and purpose: Pertussis is becoming a more and more common problem among polish children and youth. In the group of newborns and infants the pertussis course can be severe and lead to serious complications even including death from the disease (~1% <2. month old, ~0,5% 2.–11. month old). The epidemiologic analysis will allow to estimate how important and prevailing this problem is in the polish health care system.The aim of the study is to analyse the current epidemiologic situation concerning the relationship between the vaccination and incidence rate of pertussis from 1998 to 2016.Materials and method: The data used for the epidemiologic analysis were taken from the Choroby zakaźne, zakażenia i zatrucia w Polsce, raport conducted by the National Hygiene Institute.Results: In 2010 vaccination rate was 99.6% with incidence rate of pertussis about 3.32/100000. In 2016 vaccination rate dropped to 98.7% and incidence rate of pertussis reached the level of 17.77/100000.Conclusions: The dropping rate of vaccination among children and youth who are involved in the obligatory vaccination program is disturbing. The rate correlates with the increase in the pertussis incidence rate. In order to cope with this situation, the awareness among parents regarding the herd immunity and possible complications after pertussis must be increased. Herd immunity is the key to prevent spreading this disease.